Novel solid phase synthesis of a visible-light-active p-n heterojunction CuS/ZnS photocatalyst for wastewater treatment applications - Chirwa, Evans M.N. (University of Pretoria, 2024)
Dissertation (MSc (Applied Science Environmental Engineering Technology))--University of Pretoria, 2023.